On resolvable and irresolvable spaces - Chandan Chattopadhyay; Chhanda Bandyopadhyay (International Journal of Mathematics and Mathematical Sciences)
In this paper some properties of open hereditarily irresolvable spaces are obtained and the topology for a minimal irresolvable space is specified. Maximal resolvable spaces are characterized in the last section.